2013
DOI: 10.1107/s1600536813023891
|View full text |Cite
|
Sign up to set email alerts
|

6-Methoxy-4-(2,4,5-trimethoxyphenyl)-2,2′-bipyridine-5-carbonitrile

Abstract: In the title 3-cyano­pyridine derivative, C21H19N3O4, the 3-cyano-substituted pyridine ring forms dihedral angles of 2.35 (5) and 41.60 (5)° with the unsubstituted pyridine and 2,4,5-trimeth­oxy-substituted benzene rings, respectively. The dihedral angle between the unsubstituted pyridine and benzene rings is 39.84 (5)°. The meth­oxy groups form Cmeth­yl—O—C—(C,N) torsion angles in the range 0.80 (15)–11.45 (15)°. In the crystal, mol­ecules related by 21 screw axes are linked by weak C—H⋯N hydrogen bonds along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The cyano group is also roughly co-planar with the pyridine ring with an rms deviation of 0.0406 (1) Å from the ring plane. The bond distances in (I) agree with the literature values (Allen et al, 1987) and are comparable to those found in closely related structures (Chantrapromma et al, 2013 andSuwunwong et al, 2012;).…”
Section: Data Collectionsupporting
confidence: 89%
See 1 more Smart Citation
“…The cyano group is also roughly co-planar with the pyridine ring with an rms deviation of 0.0406 (1) Å from the ring plane. The bond distances in (I) agree with the literature values (Allen et al, 1987) and are comparable to those found in closely related structures (Chantrapromma et al, 2013 andSuwunwong et al, 2012;).…”
Section: Data Collectionsupporting
confidence: 89%
“…For bond-length data, see: Allen et al (1987). For related structures, see: Chantrapromma et al (2013); Suwunwong et al (2012Suwunwong et al ( , 2013.…”
Section: Related Literaturementioning
confidence: 99%